2022
DOI: 10.3389/fpsyg.2022.940076
|View full text |Cite
|
Sign up to set email alerts
|

Who Purchases From the Informal Economy and Why?

Abstract: In recent decades scholars have acknowledged that transactions in the informal economy have not vanished with modernization and industrialization as expected but rather remain an important contemporary aspect of overall production and consumption across the world, in both developing and developed countries. Yet little is known about the profile of the consumers in this realm or what drives them to purchase from the informal economy. A systematic review of the literature investigating consumption in the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The independent variables used as control variables are chosen in accordance to the specifications of previous research on trust, the informal economy and informal payments for health services ( Balabanova and McKee, 2002 ; Szende and Culyer, 2006 ; Tomini and Maarse, 2011 ; Tomini et al, 2012a , b ; Baji et al, 2013 ; Kaitelidou et al, 2013 ; Tomini and Groot, 2013 ; Riklikiene et al, 2014 ; Arsenijevic et al, 2015 ; Danyliv et al, 2015 ; Stepurko et al, 2015 ; Williams et al, 2016 ; Ai et al, 2022 ; Horodnic et al, 2022a ) and include: age, gender, educational level, income, employment status, residence area (rural or village) (details in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The independent variables used as control variables are chosen in accordance to the specifications of previous research on trust, the informal economy and informal payments for health services ( Balabanova and McKee, 2002 ; Szende and Culyer, 2006 ; Tomini and Maarse, 2011 ; Tomini et al, 2012a , b ; Baji et al, 2013 ; Kaitelidou et al, 2013 ; Tomini and Groot, 2013 ; Riklikiene et al, 2014 ; Arsenijevic et al, 2015 ; Danyliv et al, 2015 ; Stepurko et al, 2015 ; Williams et al, 2016 ; Ai et al, 2022 ; Horodnic et al, 2022a ) and include: age, gender, educational level, income, employment status, residence area (rural or village) (details in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This may be explained partly by the fact that the informal economy as a concept was born out of economic development literature (Portes, 1983) and is often measured in terms of productivity and employment. In the extant literature, the consumption side of the informal economy is often considered a means to measure production and economic development, while studies focusing on the demand side of the informal economy are limited (Horodnic, Ciobanu, et al, 2022).…”
Section: Informal Consumer Activitymentioning
confidence: 99%
“…A recent systematic literature review identified only 19 published research papers using empirical or theoretical models for consumer behaviour in the informal economy (Horodnic, Ciobanu, et al, 2022). This review does not incorporate certain, but limited in number and citations, studies in business literature (such as K. McCrohan et al, 1991;K.…”
Section: Informal Consumer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, as seen in figure 2, the variety of sciences that address the study of this object of study is wide. Observing a predominance of research in the social sciences, within which the subject is approached from edges as distant as the migratory phenomena (Fouskas, 2018;Maroukis, 2018), gender equality (Sinha & Sengupta, 2017;Zainol & Al Mamun, 2018;Takaza & Chitereka, 2022), salary differences (Kahyalar et al, 2018) and informal labour markets (Williams & Bezeredi, 2018;Goyal, 2022;Horodnic et al, 2022).…”
mentioning
confidence: 99%